Rancang Bangun Extension Prefilter Pada Sistem Udara Masuk Gas Turbine PLTGU Blok 3 Tanjung Priok - Harun Al-Rosyid; Gita Puspa Artiani (Sekolah Tinggi Teknik - PLN, 2015)
Today the need for energy is so high, and the need to electrical energy this has become a dependence, so it needs availability of supply and sustainable, big and so, it was required units power plants that have reliability. Central power gas and Steam room (PLTGU) Block 3 Tanjung Priok is one of the central electricity supplies in network system inter-connection Java and Bali that capacity 1 X 740 MW. In PLTGU there are two power systems that power plant gas and steam room. In PLTGU Block 3 Tanjung Priok uses gas turbine Mitsubishi type M701F, where there is a system to support its operations, is the System for fuel, Air Enters System gas turbine (GT water intake System) and the air, The former System GT Washing and Drain, Protection System, The Air Conditioning System instruments, Requests Injection System and water. In a system Air Enters gas turbine, there are filter-filter that functioned to filter dirt that entered into the turbine, which consists of Weather Hood, Droplet Eliminator element, and the Final Prefilter filter. Because of higher humidity, that were found in the area power plants, so that the power plant operations often take replacement Prefilter, which age use of Prefilter is near-and-a-half from the age use recommended by manufacturers Prefilter. Discussion on this project is about additional filter air before Prefilter, so it is expected to be prolongs life from Prefilter to use that is recommended to the age by manufacturers prefilter even beyond the age that is recommended by manufacturers Prefilter. That will eventually enhanced reliability power plants.